ChemInform Abstract: Ionothermal Synthesis, Structure, and Bonding of the Catena‐Heteropolycation 1∞[Sb2Se2]+. Issue 18 (May 2015) - Groh, Matthias F.; Breternitz, Joachim; Ahmed, Ejaz; Isaeva, Anna; Efimova, Anastasia; Schmidt, Peer; Ruck, Michael
Abstract Dark‐red crystals of [Sb2Se2]AlCl4 are prepared from mixtures of Sb, Se, AlCl3, and [bmim]Cl (160 °C, 7 d, up to 50% yield).